DER ER TO I ET MØDE: Perspektiver på kulturmødet fra psykiatrien - Johansen, Katrine Schepelern (Tidsskriftet Antropologi, 2007)
The psychiatric treatment system in Denmark is one of the institutions where the meeting with the ethnic Other has gained increased attention in the last couple of years. Even though this is being spoken of as a meeting, focus is normally only on the ethnic patients, their culture, and the problems staff experience when working with this group of patients. Doing anthropological research in the Danish psychiatric system, makes it obvious, however, that the psychiatric system itself plays an important part in the meeting. Psychiatry has its own way of understanding what culture is, and its own way of framing how culture can be talked about. Using a modern, relational concept of culture I will show how the psychiatric departments can be perceived as producing their own culture and that this culture plays an important part in how patients with another ethnic background than Danish are perceived. Patients who are perceived as ethnic are often patients that psychiatry finds it difficult to treat, either because the technology of treatment is not suited to this group of patients, or due to the way psychiatry perceives the relation between psychiatric disorder and culture.